Analysis of Stress State of Bolts under Different Anchorage Qualities - Zeng, Sheng; Zhou, Jie; Sun, Bing; Wen, Xia (ITB Journal Publisher, LPPM ITB, 2018)
A series of pull-out tests were conducted in order to study the stress states of bolts under different anchorage qualities and to simulate the influence of quality defects in empty-slurry and low-strength mortar anchorage in actual engineering. The tests mainly investigated strain characteristics at different positions of the bolts and the effects of strains at the same positions under different anchorage conditions. The research led to the following conclusions: (1) under ultimate bearing capacity, the strain values decayed the fastest along the length of the bolt in the full-length anchorage, the strain values decayed the slowest in the empty-slurry and low-strength mortar anchorage, and the decaying speed of strains in the empty-slurry mortar anchorage was between that of the above two kinds of anchorages; (2) at almost 50% of the ultimate bearing capacity, the strain values were slightly different between the empty-slurry and low-strength mortar anchorage and the empty-slurry anchorage. Obvious differences in strain values occurred when the bolts were continued to be loaded. The strain values of the full-length anchorage bolts were different from those of the other two kinds of anchorages; (3) from the analysis of stress variation characteristics, the safety reserve was the highest for the full-length anchorage under the condition of ultimate bearing capacity, followed by the empty-slurry mortar anchorage, while the safety reserve was the lowest for the empty-slurry and low-strength mortar anchorage. However, in terms of uniformity of force and utilization of the material, the result was reverse.